2020
DOI: 10.1111/rda.13647
|View full text |Cite
|
Sign up to set email alerts
|

Embryo gene expression in pig pregnancy

Abstract: Pregnancy is a complex process in which significant changes occur continually in both the corpora lutea and in the endometrium of the females and varies depending on the embryonic, pre‐implantation or foetal stages. In the embryonic stages, the majority of genes expressed in the pig embryo correspond to the loss of cellular pluripotency. In contrast, the implantation consists of three phases: elongation of the conceptus, adhesion and union of the embryo to the endometrial epithelium. During these phases, many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Factors such as Nanog and SRY-box transcription factor 2 ( SOX2 ) are upregulated by the Wnt pathway in ICM around Day 8 in bovine embryos, with one ( SOX2 ) or two ( Nanog ) characteristic peaks of expression in goat embryos at the 8- to 16-cell stage and later blastocyst stage, respectively. In this context, Nanog expression is necessary for the proliferation of TE cells [ 5 , 15 , 21 , 22 , 23 ].…”
Section: Pluripotency Transcription Factorsmentioning
confidence: 99%
“…Factors such as Nanog and SRY-box transcription factor 2 ( SOX2 ) are upregulated by the Wnt pathway in ICM around Day 8 in bovine embryos, with one ( SOX2 ) or two ( Nanog ) characteristic peaks of expression in goat embryos at the 8- to 16-cell stage and later blastocyst stage, respectively. In this context, Nanog expression is necessary for the proliferation of TE cells [ 5 , 15 , 21 , 22 , 23 ].…”
Section: Pluripotency Transcription Factorsmentioning
confidence: 99%
“…The definition of exosomes from the ExoCarta database for exosomes is "30-150 membrane vesicles of endocytic origin secreted by most cell types in vitro" (Keerthikumar et al, 2016). Exosome cargoes are very varied and include different types of interleukins (IL-1β, IL-6, IL-8), growth factors (vascular endothelial growth factor (VEGF), transforming growth factor (TFG) and hormones (aldosterone)), all essential for embryonic development and implantation in different species of domestic animals (Clayton et al, 2019;Llobat, 2020). Saadeldin et al (2014) found mRNA related to pluripotency (Oct4, Sox2, c-Myc and Nanog) in cultured mammalian embryos (Saadeldin et al, 2014).…”
Section: Small-evs: Exosomesmentioning
confidence: 99%
“…Saadeldin et al (2014) indicated the relevance of MVs in pig embryo communication. These microvesicles contain mRNAs essential for early embryonic development (Llobat, 2020;Saadeldin et al, 2014).…”
Section: Early Embryo Development and Oviduct Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of pregnancy is a complex physiological process. A series of structural and functional changes must occur in the maternal uterus at the early stage of the establishment of pregnancy to enable the implantation of early embryos and the growth and development of the foetuses [ 2 , 3 ]. The steady state of the intrauterine environment is also an important condition for successful pregnancy and normal foetal growth and development [ 4 ].…”
Section: Introductionmentioning
confidence: 99%